If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 235 = 60X Solving 235 = 60X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-60X' to each side of the equation. 235 + -60X = 60X + -60X Combine like terms: 60X + -60X = 0 235 + -60X = 0 Add '-235' to each side of the equation. 235 + -235 + -60X = 0 + -235 Combine like terms: 235 + -235 = 0 0 + -60X = 0 + -235 -60X = 0 + -235 Combine like terms: 0 + -235 = -235 -60X = -235 Divide each side by '-60'. X = 3.916666667 Simplifying X = 3.916666667
| a+x=5a | | 10-4t=-6t | | 63-3=n-5 | | 2(3r-3)=-22+8r | | -8x+3=14 | | -53-9x=35-5x | | 26=x/-5 | | 4j-3=5j | | 5(-7-6n)=-10-5n | | x^2+4x+8=8x+29 | | 2x=.36 | | 5/9(240) | | 3/7+2/5x=1/5x+1 | | 9h+6=10h | | -28=-x+11-(-5) | | -1/5r=-20 | | 5(t+2)=3.2k | | p^2=3p+28 | | (2x+1)*2+(x+1/2)*2=18 | | 5x+10=30whatisx | | 3x-12+2x=13 | | 11.3-72f=-3.82 | | 2k+k=-9 | | 2k=-9k^2-10 | | 11y-7y-10=73.92 | | -x^2y= | | 3+7x-5=4x-12 | | 5p-12-3(p+8)=4 | | f(-3)=-2(3x-2)+x+9 | | 3-7(-2)-8= | | -7w=42 | | 15x+x=192 |